Ownership, Privacy and Monitoring in the Workplace: A Debate on Technology and Ethics - Loch, Karen D. (Journal of business ethics, 1998)
A panel held at the International Conference on Information Systems, December 5–7, 1993, addressed the importance and ethicality of several issues relating to ethics and information technology use. The substance of the debate and results of audience votes on the issues are presented in this paper as a means of initiating a broader debate on the issues, for it is with debate that we reach a group consensus on acceptable behavior and practice. With consensus, we can begin to develop codes and policies that are feasible and practical for ethical computer use., Specific dilemmas debated involved the issues of privacy and ownership, including the ethicality of using company resources for personal use and monitoring compliance to company policies about computer use. In general, we found little consensus about ethicality of any of the types of conduct, although we found a high degree of consensus that the debated issues were important and should continue to be discussed. The final question concerned policies and codes. While policies and codes were believed to be necessary, they were also perceived as ineffective. Several suggestions for practical action to enhance the efficacy of ethical codes are presented.